Structural Connectivity and Cortical Thickness Alterations in Transient Global Amnesia - Hodel, J.; Leclerc, X.; Zuber, M.; Gerber, S.; Besson, P.; Marcaud, V.; Roubeau, V.; Brasme, H.; Ganzoui, I.; Ducreux, D.; Pruvo, J.-P.; Bertoux, M.; et al. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Transient global amnesia (TGA) is a sudden onset of anterograde and retrograde amnesia. We aimed to assess differences in terms of cortical thickness and structural brain connectome between patients with TGA (at acute and delayed postrecovery stages) and matched controls.MATERIALS AND METHODS: We report on 18 consecutive patients with TGA who underwent 3T MR imaging, including DTI and MPRAGE sequences, at the acute (mean delay postonset: 44 hours) and delayed post-recovery (mean delay: 35 days) stages. Structural connectome was assessed in patients with TGA and in 18 age- and sex-matched controls by using probabilistic fiber- tracking and segmentation of 164 cortical/subcortical structures (“nodes”). Connectivity graphs were computed and global network metrics were calculated. Network-based statistical analysis (NBS) was applied to compare patients with TGA at each stage with controls. We also compared cortical thickness between patients with TGA and healthy controls.RESULTS: Global network metrics were not altered in patients with TGA. NBS-analysis showed structural connectome alterations in patients with TGA compared with controls, in core regions involving the limbic network, with 113 nodes and 114 connections (33 left intrahemispheric, 31 right intrahemispheric, and 50 interhemispheric connections) showing significantly decreased structural connectivity (P < .05 NBS corrected, t-values ranging from 3.03 to 8.73). Lower cortical thickness compared with controls was associated with these structural alterations in patients with TGA, involving the orbitofrontal, cingulate, and inferior temporal cortices. All the abnormalities were visible at both acute and delayed postrecovery stages.CONCLUSIONS: Our preliminary study suggests there are structural abnormalities of the limbic network in patients with TGA compared with controls, including decreased structural connectivity and cortical thickness.TGAtransient global amnesiaTOF-MRAtime-of-flight MRAVBMvoxel-based morphometryAUCarea under the curveFDRfalse discovery rateNBSnetwork-based statistical analysis